The ‘Pentol Bakar’ Application as an Innovative Approach in Mental Health Emergencies : A Scoping review - Ryka Widyaningtyas (Fakultas Keperawatan Universitas Andalas, 2025)
The issue of mental health disorders is a complex problem that requires serious attention. The